Evaluating acidithiobacillus ferrooxidans bacterial oxidation of sulphur compounds using ftir and x-ray diffraction assays (2003)
A native bacterial strain capable of oxidising ferrous iron and sulphur compounds was isolated from effluent and material from the La Maruja gold mine in the municipality of Marmato (Caldas); this was biochemically identified as being Acidithiobacillus ferrooxidans. This strain's ability to oxidise metallic sulphide concentrates having two differ-ent pulp proportions and two particle sizes was evaluated. Sulphide bio-oxidation was observed after 15 days showing this strain's catalytic action on the mineral break-down process. Key words: bio-oxidation; bio-leaching; A. ferrooxidans; sulphides